2015
DOI: 10.1186/s12936-015-1060-1
|View full text |Cite
|
Sign up to set email alerts
|

Computer-vision-based technology for fast, accurate and cost effective diagnosis of malaria

Abstract: BackgroundMicroscopy has long been considered to be the gold standard for diagnosis of malaria despite the introduction of newer assays. However, it has many challenges like requirement of trained microscopists and logistic issues. A vision based device that can diagnose malaria, provide speciation and estimate parasitaemia was evaluated.MethodsThe device was evaluated using samples from 431 consented patients, 361 of which were initially screened by RDT and microscopy and later analysed by PCR. It was a prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…In a previous study [22] we presented the first clinically available computer vision based reader for malaria diagnostics. The P1 device showed a sensitivity of 97.05%, specificity of 96.33% and speciation of 73.3% Plasmodium falciparum and 91.4% for Plasmodium vivax.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study [22] we presented the first clinically available computer vision based reader for malaria diagnostics. The P1 device showed a sensitivity of 97.05%, specificity of 96.33% and speciation of 73.3% Plasmodium falciparum and 91.4% for Plasmodium vivax.…”
Section: Discussionmentioning
confidence: 99%
“…Previous attempts at a creating a computer microscopist have not surpassed the development stage [20,21]. A recent report from our group, described a clinically available automated microscopist which was tested with the National Institute of Malaria Research India [22]. The device, the SightDx P1 malaria platform, was tested on 431 patients and demonstrated a sensitivity of 97.05%, and a specificity of 96.33% when compared with PCR.…”
Section: Introductionmentioning
confidence: 99%
“…Microscopy Mixed 12 0 0 0 12 Negative 0 42 3 5 50 pf 0 0 10 0 10 pv 0 0 0 28 28 Total 12 42 13 33 0 0 6 Negative 3 42 5 12 62 pf 1 0 8 0 9 pv 2 0 0 21 23 Total 12 42 13 33 100 The Parasight digital cytometry-based scanning and detection system for malaria has shown promising results in previous studies. 10,11 We tested it for practical feasibility in terms of accuracy, cost effectiveness and rapidity. Our study has shown that in comparison to gold standard microscopy, the digital cytometry gave similar results (in terms of accurate species detection as well) when parasite concentration was on higher side (mean 0.0515%).…”
Section: Rapid Diagnostic Tests (Rdt) Vs Digital Cytometrymentioning
confidence: 99%
“…At the time of publication device didn't had the algorithms to identify mixed infection. 11 Since then the data has accumulated and the sensitivity and specificity has improved in terms of detection of mixed infections. It is very important to note that all three modalities -microscopy, digital cytometry and RDT usage was done in practical scenarios.…”
Section: Rapid Diagnostic Tests (Rdt) Vs Digital Cytometrymentioning
confidence: 99%
“…Recently, our group published two studies showing that a prototype of such a system could be successful. Srivastava et al presented the prototype system (P1), which showed performance results comparable to those of many marketed RDTs (18). A follow-up article introduced the improved system (P2), which achieved sensitivity, specificity, and species identification results comparable to those of expert human microscopists (19).…”
mentioning
confidence: 99%